2013
DOI: 10.1371/journal.pone.0072646
|View full text |Cite
|
Sign up to set email alerts
|

Male Weasels Decrease Activity and Energy Expenditure in Response to High Ambient Temperatures

Abstract: The heat dissipation limit (HDL) hypothesis suggests that the capacity of endotherms to dissipate body heat may impose constraints on their energy expenditure. Specifically, this hypothesis predicts that endotherms should avoid the detrimental consequences of hyperthermia by lowering their energy expenditure and reducing their activity in response to high ambient temperatures (Ta). We used an extensive data set on the daily energy expenditure (DEE, n = 27) and the daily activity time (AT, n = 48) of male wease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 58 publications
2
15
0
Order By: Relevance
“…Similarly, it has been reported that activity levels in ungulates decrease during low T a and thus reduce energy expenditure substantially (Arnold et al, 2004;Kuntz et al, 2006;Signer et al, 2011). This reduction in activity leading to reduced daily energy demands is also observed in small mammals living in the temperate/arctic zone, such as red squirrels (Tamiasciurus hudsonicus) (Humphries et al, 2005) and least weasels (Mustela nivalis) (Zub et al, 2013), but not kangaroo rats (Dipodomys merriami) (Nagy and Gruchacz, 1994) or white-footed mice …”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Similarly, it has been reported that activity levels in ungulates decrease during low T a and thus reduce energy expenditure substantially (Arnold et al, 2004;Kuntz et al, 2006;Signer et al, 2011). This reduction in activity leading to reduced daily energy demands is also observed in small mammals living in the temperate/arctic zone, such as red squirrels (Tamiasciurus hudsonicus) (Humphries et al, 2005) and least weasels (Mustela nivalis) (Zub et al, 2013), but not kangaroo rats (Dipodomys merriami) (Nagy and Gruchacz, 1994) or white-footed mice …”
Section: Discussionmentioning
confidence: 66%
“…Lower energy requirements during winter, and hence reduced voluntary food intake, is widespread amongst Northern ungulates (Arnold et al, 2004). It has been postulated that domesticated horses may modulate their energy requirements to match insufficient energy intake (Kienzle et al, 2010), as has been shown for humans (Dulloo and Girardier, 1990;Martin et al, 2011;Rickman et al, 2011;Racette et al, 2012) and other mammalian species in captivity (reviewed in Speakman and Mitchell, 2011) and in the wild (Humphries et al, 2005;Zub et al, 2013). A reduction in energy intake of an individual below the level of requirement results in a series of physiological and behavioural responses that are beneficial to the survival of the individual (Shetty, 1984;Shetty, 1999).…”
Section: Research Articlementioning
confidence: 99%
“…Specifically, while increases in T b at high T a have been shown to reduce the energetic costs and increase the efficiency of evaporative cooling in birds and some small desert mammals [32,33,79,80], the interplay between water loss, T b and T a at the upper limits of the TNZ are largely unknown in mammals. Additionally, very little has been done to equate upper limits measured in the lab to conditions experienced by the animals under natural conditions (but see [42,81]). …”
Section: Daily Variability In Mammalian T Bmentioning
confidence: 99%
“…Considerable attention has been given to the extrinsic and intrinsic factors that might limit energy acquisition and expenditure, such as food availability and the capacity to digest and assimilate food Hammond and Diamond 1997;Speakman 2000;Bacigalupe and Bozinovic 2002), whereas only recently has the putative role of heat dissipation been recognized (but see Greenwood and Wheeler 1985). As a consequence of the heat dissipation limit theory (Speakman and Król 2010a, b), an increasing number of studies are currently assessing how heat dissipation might impact the ecology and evolution of endothermic lineages (e.g., Voigt and Lewanzik 2011;Greenberg et al 2012;Kurnath and Dearing 2013;Larose et al 2013;Zub et al 2013;Okrouhlík et al 2015).…”
Section: Activity and Reproductionmentioning
confidence: 99%